Role of psychosocial reserve capacity in anxiety and depression in patients with systemic lupus erythematosus. (6th March 2017) - Zamora‐Racaza, Geraldine; Azizoddin, Desiree R.; Ishimori, Mariko L.; Ormseth, Sarah R.; Wallace, Daniel J.; Penserga, Ester G.; Sumner, Lekeisha; Ayeroff, Julia; Draper, Taylor; Nicassio, Perry M.; Weisman, Michael H.
Abstract: Aim: To examine the relationship between reserve capacity measures and anxiety/depression among patients with systemic lupus erythematosus (SLE) from Southern California (SoCal), United States and Manila, Philippines. Methods: A total of 235 participants with SLE completed self‐reported scales to assess anxiety/depression and psychosocial reserve capacity measures (self‐esteem, optimism, personal mastery/coping skills, social support), socioeconomic status (SES) data, and Mexican SLE Disease Activity Index. Statistical analyses included independent sample t ‐tests, Chi‐square, and point‐biserial and Pearson correlations. Results: Overall, participants from Manila reported lower SES than SoCal participants. Over half of Manila and SoCal participants (69% and 59.1%, respectively) reported high anxiety scores. SoCal participants had higher depression scores than Filipinos (66%, 27%, respectively, P < 0.001) despite appearing to be more resilient by exhibiting higher scores for all reserve capacity measures ( P < 0.001). Participants with low self‐esteem scores from both groups had higher anxiety and depression scores. SoCal participants who reported lower optimism, lower personal mastery and lower social support were more anxious and depressed, while Filipinos low on these three variables reported less depressive symptoms. Conclusion: Reduced psychosocial reserve capacity in individuals leads to vulnerabilities that may ultimately result in greater disease burden and psychological distress. Low self‐esteem, optimism, coping and social support were associated with depression and low self‐esteem was associated with anxiety for both groups. Despite the Filipino cohort's lower reserve capacity and SES, Filipino patients exhibited less depression than their SoCal counterparts, suggesting that other factors may protect them from experiencing depression.